CORRELATION BETWEEN THE LENGTH OF THE DENTAL ROWS AND THE TOPOGRAPHOANATOMIC INDICATORS OF THE ARTICULAR DISK (MENISCUS) IN THE PATIENTS WITH DYSFUNCTIONAL CONDITIONS ACCORDING TO MRI DATA - Y.S. Lunkova; O.B. Tumakova; V.M. Novikov (Український стоматологічний альманах)
Objective is to investigate the interconnections of the mesiodistal dimensions of occlusal surfaces of teeth and structural elements of the temporomandibular joint with its internal disorders.